Beyond the battlefield : the new military professionalism - Sarkesian, Sam C. (Sam Charles), 1927-2011 (Pergamon policy studies on international politics., 1981)
Beyond the Battlefield: The New Military Professionalism presents the nature and character of military professionalism. This book describes the increasing tendency for the military to view professionalism mainly in terms of military skills. Organized into five parts encompassing 13 chapters, this book begins with an overview of the various concepts and definitions of military professionalism. This text then reexamines military professionalism in the post-Vietnam era with regard to perspectives on value convergence and empathy between military and society. Other chapters consider the changes in.